A hybrid method using kinect depth and color data stream for hand blobs segmentation - Karbasi, Mostafa; Muhammad Yusof, Zulkefli; Waqas, Ahmad; Bhatti, Zeeshan; Shah, Asadullah; Koondhar, M.Y.; Brohi, Imtiaz Ali (Science International, 2017)
The recently developed depth sensors such as Kinect have provided new potential for human-computer interaction (HCI) and hand gesture are one of main parts in recent researches. Hand segmentation procedure is performed to acquire hand gesture from a captured image. In this paper, a method is produced to segment hand blobs using both depth and color data frames. This method applies a body segmentation and an image threshold techniques to depth data frame using skeleton data and concurrently it uses SLIC super-pixel segmentation method to extract hand blobs from color data frame with the help of skeleton data. The proposed method has low computation time and shows significant results when basic assumption are fulfilled.